The Nibelungenlied : Revised Edition - Lettsom, William Nanson, 1796-1865; Carpenter, William H. (William Henry), 1853-1936 (Salt Lake City, UT : Project Gutenberg, 2012)
"The Nibelungenlied" by William Nanson Lettsom and William H. Carpenter is a monumental epic poem written in the late 12th century. This work of literature offers a rich tapestry of Germanic mythology and history, focusing on themes of love, betrayal, revenge, and the tragic fate of its characters. The story follows the fates of iconic figures such as Kriemhild, Siegfried, Hagen, and the kings of Burgundy against a backdrop of heroic deeds and ruin. The opening of "The Nibelungenlied" introduces us to Kriemhild, a noble maiden of unparalleled beauty and virtue, who is forewarned by a troubling dream that foreshadows tragedy. The narrative establishes her family, the kings of Burgundy, and their noble lineage, highlighting their strength and valor, then shifts to Siegfried, a hero of great renown from the Netherlands. We see the beginnings of Kriemhild and Siegfried's destinies intertwining, setting the stage for the fateful events that will lead to conflict and tragedy. The tone is both epic and intimate, as it merges grand historical themes with personal narratives, effectively foreshadowing the chaos that will ensue as loyalties are tested and vengeance is sought. (This is an automatically generated summary.)
Release date is 2012-01-02
E-text prepared by Juliet Sutherland, Rory OConor, and the Online Distributed Proofreading Team
Keywords: Epic poetry, German -- Translations into English; Nibelungen -- Poetry